DEVELOPMENT OF METAVERSE CLASSROOM WITH GAMIFICATION CONCEPT TO ENHANCE STUDENT’S COMPUTATIONAL THINKING SKILLS OF UPPER PRIMARY SCHOOL - Wingsakul, Sureerat; Rampai, Nattaphon; Diteeyont, Watsatree (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article is a research about the to develop Metaverse Classroom with Gamification Concepts to Enhance Student’s Computational Thinking Skills of Upper Primary School, ensuring appropriateness and effectiveness according to the 80/80 criteria, 2) to study student’s computational thinking skills that studying in a classroom with gamification concepts, 3) to study the effectiveness index of the Metaverse Classroom together with the concept Gamification that enhances computational thinking skills of students in upper primary school level, and 4) to study student’s satisfaction with the Metaverse Classroom combined with the concept of gamification. that enhances computational thinking skills. The sample group used in this research were 5th grade students. Those studying computational science, semester 1, academic year 2023, totaling 26 people, using a cluster random sampling. The research tools were 1) Metaverse Classroom combined with gamification concepts 2) Pretest and postest measure computational thinking skills. and 3) Satisfaction questionnaire. Data were analyzed by percentage, mean, Standard Deviation, t - test, and effectiveness index. The research results were 1) the Metaverse Classroom with Gamification Concepts to Enhance Computational Thinking Skills for Upper Primary School Students showed quality at highest level and shared efficiency at 80/80, 2) the student’s computational thinking skill scores after studying were significantly higher than the students pre-test scores at the .05 level, 3) the Effectiveness Index (E.I.) of the Metaverse Classroom was 0.82, indicating that students had increased academic progress., and 4) the student’s satisfaction with the Metaverse Classroom with gamification concepts. at the highest level.